RETHINKING TEACHERS"™ PROFESSIONAL DEVELOPMENT: LESSON FROM EVALUATION IN MASTER PROGRAM OF MATHEMATICS EDUCATION - Rif'at, Mohamad; Siregar, Nurfadilah (Jurnal Pendidikan Matematika dan IPA, 2022)
This research is based on the results of the evaluation of the last ten years related to the development of studies in the Mathematics Education Master Program, Tanjungpura University, through a partnership model to develop and implement national and international comparative studies on mathematics teacher education. The aims are to describe the methodology used in the national level study of teacher education through the Teacher Professional Education Program or Pendidikan Profesi Guru (PPG)- Teacher Education and Development of Studies in Mathematics and share key findings related to mathematics preparation for future teachers. The research applied a quantitative approach with cross-sectional survey method with students of the master program of mathematics education class of 2019/2022 and 2020/2021. The results of the study show that future teacher performance: (1) has less opportunity to learn than high achievers in geometry, functions, calculus, and groups with mastery of linear algebra, number theory, analytic geometry, introduction to probability, and statistics and (2) has less opportunity for those who study school mathematics in data representation, calculus compared to linear algebra, analytic geometry, introduction to calculus, calculus, probability, and statistics. Thus, it can be concluded that attention and emphasis are needed on the type and depth of learning materials given to future teachers who continue their studies at the master's level. This pattern represents an extension to better future secondary school teachers.